Comparative metagenomic analysis of human intervertebral disc nucleus pulposus and cartilaginous end plates - Shanmuganathan, Rajasekaran; Tangavel, Chitraa; K S, Sri Vijay Anand; Muthurajan, Raveendran; Nayagam, Sharon Miracle; Matchado, Monica Steffi; Rajendran, Sunmathi; Kanna, Rishi Mugesh; Shetty, Ajoy Prasad (Frontiers in Cardiovascular Medicine, 2022)
Study Design: The diversity of microflora inhabiting endplate (EP) and nucleus pulposus (NP) tissues of human IVD was profiled using NGS-aided 16S rRNA amplicon sequencing. Objectives: 1) To understand whether the colonization of bacteria to the NP is through the EP in discs with intact annulus fibrosus 2) To identify significantly differing microbial population(s) between healthy and diseased IVD (NP) Background of the study: There is increasing evidence for subclinical infection by fastidious low, growing bacteria as a cause of disc degeneration. Although the presence of bacteria in NP has been reported well in literature, the source of bacteria is not clearly proved as the disc is avascular in healthy condition. Documentation of similar bacterial populations in the EP and NP may add proof that bacterial inoculation of NP occurs via the EP. Materials and Methods:Sixteen NP and 16 EP tissues excised from brain-dead voluntary organ donors with no history of back pain and 20 diseased discs (12 herniated and 8 degenerated NP tissues) collected from patients undergoing microdiscectomy/ fusion surgery. Results: NP and EP shared a similar spectrum of microbiome but with varying abundance. The five dominant phyla identified were Proteobacteria, Firmicutes, Actinobacteria, OD1, and Bacteroidetes. Proteobacteria was found to be the most abundant phyla in both NP (62%) and EP (53%) of the normal IVD and in diseased states (68%) compared with other phyla. However, there was no significant difference in the abundance of Proteobacteria between conditions. Interestingly, the other dominant phyla such as Firmicutes and Actinobacteria showed a significant reduction in degenerated discs. To understand their significant alteration during disease, correlation analysis revealed a negative correlation in the ratio of Actinobacteria + Firmicutes vs. Proteobacteria (p = 0.001) in DD. Conclusion: Results of our study clearly demonstrated a similar bacterial diversity but with varying abundance between the EP and NP, suggesting the existence of the endplate – nucleus pulposus axis in the healthy IVD microbiome. Further, our results have indicated that the changes in the abundance of Actinobacteria + Firmicutes vs. Proteobacteria during DDD may be of potential significance and needs further investigation.